2010
DOI: 10.2478/s11756-010-0113-8
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analysis of a type III polyketide synthase gene in Fallopia multiflora

Abstract: A type III polyketide synthase (PKS) cDNA and the corresponding gene (FmPKS) were isolated from the rhizomes of Fallopia multiflora (Thunb.) (Polygonaceae). The full-length FmPKS cDNA was 1,228 bp, containing an open reading frame of 1,137 bp encoding a 378 amino acid residues long protein. The coding sequence of the gene was interrupted by three introns, a different gene structure from most of the type III PKS genes studied so far containing only one intron at a conserved site, except for the recently cloned … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
10
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 24 publications
(23 reference statements)
2
10
0
Order By: Relevance
“…To our knowledge, this is the first report that an STS gene from F. multiflora transferred to other plants leads to stilbene accumulation. Considering the relevance of the FmSTS1 expression pattern with the distribution of THSG reported in our previous research (Sheng et al 2010), FmSTS1 may play a crucial role in stilbenes biosynthesis in F. multiflora and may directly affect THSG biosynthesis. Further research will focus on its transformation into F. multiflora cell line or hair root to confirm whether it can improve THSG production.…”
mentioning
confidence: 60%
See 2 more Smart Citations
“…To our knowledge, this is the first report that an STS gene from F. multiflora transferred to other plants leads to stilbene accumulation. Considering the relevance of the FmSTS1 expression pattern with the distribution of THSG reported in our previous research (Sheng et al 2010), FmSTS1 may play a crucial role in stilbenes biosynthesis in F. multiflora and may directly affect THSG biosynthesis. Further research will focus on its transformation into F. multiflora cell line or hair root to confirm whether it can improve THSG production.…”
mentioning
confidence: 60%
“…Our team has performed considerable research aimed at characterizing the THSG biosynthesis mechanism (Xia et al 2017). We previously showed that the expression pattern of FmSTS1 analyzed by Northern blot corresponded well with the THSG distribution in different tissues of F. multiflora, implying that FmSTS1 may play a crucial role in THSG biosynthesis (Sheng et al 2010). In the current study, the anticipated THSG was not detected in the transgenic Arabidopsis.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Firstly, the possible relevant genes or enzymes should be identified from Polygonum multiflorum. The clone of a type Ш polyketide synthase gene (FmPKS) using oligonucleotide primers designed for regions conserved amongst STS (with special attention given to the closely-related species of the Polygonaceae family) in Fallopia multiflora have be conducted by Shujing Sheng [51]. The FmPKS has been identified strongly correlates with the accumulation of stilbene glucoside by using Northern blotting, RNA inference and over expression, suggesting that FmPKS might play an important role in its biosynthesis.…”
Section: The Application Of Systems Biology Approaches In Research Onmentioning
confidence: 99%
“…Up to now, no enzyme was found to catalyze the biosynthesis of THSG. Sheng et al THSG was still not detectable in transgenic Arabidopsis thaliana in which FmPKS was inserted and expressed [11]. Shao et al showed precursor feeding of methyl jasmonate and salicylic acid in suspension cultures of F. multiflora that could increase THSG production [12].…”
Section: Introductionmentioning
confidence: 99%